Bromidovanadium(II, III, and IV) Complexes. Issue 8 (25th March 2013) - Rehder, Dieter; Nekola, Henning; Behrens, Axel; Cramer, Stephen P.; Funk, Tobias
Abstract The bromidovanadium complexes cis‐[VIIBr2(bith)] (1) [bith = 1, 6‐bis(2‐benzimidazolyl)‐2, 5‐dithiahexane], cis‐[VIIBr2(pth)] (2a) [pth = 1, 6‐bis(2‐pyridyl)‐2, 5‐dithiahexane], cis‐[VIIIBr2(pth)]Br (2b), trans‐[VIIBr2(tmeda)2] (3) (tmeda = tetramethylethylenediamine), fac‐[VIIIBr3(9S3)] (4) (9S3 = 1, 4, 7‐trithiacyclononane), mer‐[VIIIBr3(thf)3] (5) (thf = tetrahydrofurane), and trans‐[VIVOBr2(thf)2H2O] (6) were prepared and characterized by, inter alia, XRD (5, 6), K‐edge XAS (3, 4) or L‐edge XAS (2a, 2b). The complexes are also addressed in the context of the potential of halogenidovanadium compounds in catalytically conducted reactions, including biogenic processes.